2012
DOI: 10.1590/s0104-11692012000200017
|View full text |Cite
|
Sign up to set email alerts
|

The ferric aerobactin receptor IutA, a protein isolated on agarose column, is not essential for uropathogenic Escherichia coli infection

Abstract: Although many proteins have been described involved in Escherichia coli colonization and infection, only few reports have shown lectins as important components in these processes. Because the mechanisms underlying E. coli colonization process involving lectins are not fully understood, we sought to identify the presence of other non-described lectins in E. coli. Here, we isolated a 75-kDa protein from E. coli on Sepharose column and identified it as ferric aerobactin receptor (IutA). Since IutA is cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…These replicons were present in isolates from both the environment and clinical samples (Additional file 2: Figure S1). Of the 75 virulence factors considered, 10 were present in >95% of isolates, examples being the mrk genes encoding fimbrial biosynthesis proteins and iutA encoding ferric aerobactin receptor [32]. By contrast, more than 40% of virulence genes were exclusively present in the clinical isolate collection (Additional file 2: Figure S2), including genes involved in capsule synthesis ( rmpA ) [33], iron transport ( iro ), phospholipid transport ( mce ), regulation and transport (multiple clb genes), and transcription regulation ( kvgA ).…”
Section: Resultsmentioning
confidence: 99%
“…These replicons were present in isolates from both the environment and clinical samples (Additional file 2: Figure S1). Of the 75 virulence factors considered, 10 were present in >95% of isolates, examples being the mrk genes encoding fimbrial biosynthesis proteins and iutA encoding ferric aerobactin receptor [32]. By contrast, more than 40% of virulence genes were exclusively present in the clinical isolate collection (Additional file 2: Figure S2), including genes involved in capsule synthesis ( rmpA ) [33], iron transport ( iro ), phospholipid transport ( mce ), regulation and transport (multiple clb genes), and transcription regulation ( kvgA ).…”
Section: Resultsmentioning
confidence: 99%
“…29 Landgraf et al reported that relation between iutA gene and uropathogenics was low. 32 Also, salmochelin (iroN) was found higher than ferric aerobactin (iutA) in several types' urinary tract infections. 11,28 In our study, presence of aer and iutA gene regions in many types of clinical strains and iroN gene in urine shows that this gene is a siderophore specific to urinary tract infection.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, since iron acquisition systems are assumed to be functionally redundant (Garcia et al, 2011;Landgraf et al, 2012), the role of aerobaction in the virulence of APEC need further investigation. As is known to all, the aerobactin operon is consisted of four biosynthesis genes iucABCD and one receptor gene iutA, However, prior to our studies, aside from the whole iucABCDiutA operon or the single iutA aerobactin receptor, the individual roles of iuc-containing genes in the virulence of APEC have seldom been investigated.…”
Section: Discussionmentioning
confidence: 99%